Design and Analysis of an Ultra-Wideband High-Precision Active Phase Shifter in 0.18 μm SiGe BiCMOS Technology - Hao Jiang; Zenglong Zhao; Nengxu Zhu; Fanyi Meng (Journal of Low Power Electronics and Applications)
This paper presents an active phase shifter for phased array system applications, implemented using 0.18 μm SiGe BiCMOS technology. The phase shifter circuit consists of a wideband quadrature signal generator, a vector modulator, an input balun, and an output balun. To enhance the bandwidth, a polyphase filter is employed as the quadrature signal generator, and a two-stage RC-CR filter with a highly symmetrical miniaturized layout is cascaded to create multiple resonant points, thus extending the phase shifter’s bandwidth to cover the required range. The gain of the variable-gain amplifier within the vector modulator is adjustable by varying the tail current, thereby enlarging the range of selectable points, improving phase-shifting accuracy, and reducing gain fluctuations. The measurement results show that the proposed active phase shifter achieves an RMS phase error of less than 2° and a gain variation ranging from −1.2 dB to 0.1 dB across a 20 GHz to 30 GHz bandwidth at room temperature. The total chip area is 0.4 mm2, with a core area of 0.165 mm2, and consumes 19.5 mW of power from a 2.5 V supply.